Dance nos. 1 and 3 - Glass, Philip 1937-; Philip Glass Ensemble (USA) (New York Tomato, 1980)
The music on this album was originally conceived as a three-way collaboration between composer Philip Glass, choreographer Lucinda Childs and artist Sol LeWitt. "Dance" received its world premiere in Amsterdam on October 19th, 1979 and its New York premiere at the Brooklyn Academy of Music on November 29th, 1979.
Ex libris Willie Verdievel & Gemeentelijke Discotheek Wevelgem (sticker)
Keywords: 20th Century (1901-2000); Minimalist music; Dance; USA